The CARIFORUM-EU Economic Partnership Agreement (EPA) : an assessment of issues relating to market access, safeguards and implications for regional integration (ECLAC Port of SpainTT, 2008)
Focuses on market access, the impact on tariff revenues, and the implications for regional integration. Seeks to clarify and distil some of the main contentious issues regarding the EPA and to inform further discussions regarding an implementation plan.
Keywords: ACCESS TO MARKETS